"The gerontology of suffering and its social remediation: a Buddhist perspective". Issue 4 (2nd October 2019) - Chang, Adrienne
ABSTRACT: While suffering is often assumed to be an intractable aspect of growing old, gerontological work on older adults' experiences of suffering remains limited, and there is a stated need for more conceptual clarity on the construct of suffering. Buddhism provides a unique religious and philosophical perspective to understanding suffering's complex relations to physical and emotional pain, the inevitability of change, and to notions of self. This paper explores current gerontological research on suffering and analyzes how Buddhism may offer new insights and techniques into understanding the experience of suffering in later life and, most importantly, the social response it calls forth.